2016
DOI: 10.5114/aoms.2015.55146
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between visual status and functional status and the risk of falls in women. The RAC-OST-POL study

Abstract: IntroductionFalls in elderly women producing fractures are a public health problem that could be largely preventable. The aim of this study was to determine the effect of visual impairment on functional status, falls and fractures in women.Material and methodsWe examined 623 women aged ≥ 55 years in order to assess the association between visual status and functional status and the risk of falls and fractures. Distance, near visual acuity, and depth perception were examined. Functional status was assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Risk of falling increases with aging due to the progression of physiological changes such as decreases in vision and hearing perceptions, decreases in motor strength as well as due to the medications being used [36, 37]. It has been stated that this risk is higher in patients above 75 years of age [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Risk of falling increases with aging due to the progression of physiological changes such as decreases in vision and hearing perceptions, decreases in motor strength as well as due to the medications being used [36, 37]. It has been stated that this risk is higher in patients above 75 years of age [11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Sensory impairments, including visual and/or hearing impairments, are associated with several problems that can arise in old age. Primarily, research has reported an association between vision and increased frequency of falls and an increase in the risk of recurrent falls in older women due to visual impairment [ 15 , 16 ]. Furthermore, greater frailty, measured by gait speed, grip strength, peak expiratory flow rate, and the ability to rise from a chair without arm support, is associated with poorer visual functions [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This cohort was then studied in regard to various aspects of bone health. [2][3][4][5][6][7][8][9][10][11][12] More recently, we presented data from a large group of female patients enrolled when attending a single outpatient osteoporosis clinic; this research was published in consecutive papers and identified with the acronym GO Study. [13][14][15] In recent years, methods for fracture risk assessment were developed, 12,[16][17][18] and fracture risk assessment became an important part of the examination of patients.…”
Section: Introductionmentioning
confidence: 99%